Five new species of the longulus-group of Hydroporus Clairville, 1806 from north-eastern Turkey (Coleoptera: Dytiscidae) - Fery, Hans; Erman, Ömer Köksal (Zootaxa, 2009)
Hydroporus artvinensis sp. n., H. cagrankaya sp. n., H. lundbergi sp. n., H. sivrikaya sp. n., and H. toledoi sp. n. (Coleoptera: Dytiscidae) are described from north-eastern Turkey. All five species belong to the longulus-group of Hydroporus Clairville, 1806. They are externally very similar and only the males can be distinguished with certainty by the shape of their aedeagi. These are figured for all five new species, together with the female genitalia of H. cagrankaya sp. n. The males of the species have the proand mesotarsi provided with sucker cups, what is demonstrated for H. cagrankaya sp. n. by some SEM photos. The DNA of this species was also studied; the results suggest a close relationship with H. dobrogeanus Ieniştea, 1962, H. gueorguievi Wewalka, 1975, H. kraatzii Schaum, 1868, and H. sardomontanus Pederzani, Rocchi & Schizzerotto, 2004. The present data indicate an allopatric distribution for the new species, each occurring in a rather restricted area. Except H. artvinensis sp. n., they have been found on the northern slope of the Doğu Karadeniz Dağlari, a mountain range south of the coast of the Black Sea. The number of Turkish Dytiscidae is raised to about 145 species and that of the endemic taxa to 23. The total number of the members of the longulus-group increases from 18 to 23 species. Finally, some new records are presented for H. erzurumensis Erman & Fery, 2000.